Effect of altitude training on runner's skeletal muscle - Stray-Gundersen, J.; Levine, B.; Bertocci, L. A. (Medicine & Science in Sports & Exercise, 1999)
High altitude affects the body's physiology but athletes rarely train at such altitudes. This study investigated the effects of customary training altitudes; low (1,000-2,000 m) and moderate (2,000-3,000 m), on histologic and biochemical factors in the m. vastus lateralis of trained runners (M = 27; F = 12). Muscle biopsies were taken before four weeks of a control condition of sea level training and then after another four weeks after Ss had been divided in sea level (N = 13), low altitude (1,250-1,600 m; N = 13), and moderate altitude (2,200-3,00 m; N = 13) living groups. In the control condition the groups were similar. Training volume and relative intensity were not different between periods. In the experimental phase, - interval VO2 and velocity were lower at moderate altitude; - VO2max improved at both altitudes; - 5,000-m time-trial improved only in the low altitude group; - fiber type areas were less during the control sea level phase, but were higher in all groups during the experimental phase; - percent fiber type and capillary density did not change in any group or living experience; - no enzymes changed except for PFK activity in the sea level group during the experimental period; and - tissue buffer capacity decreased the moderate altitude group. Implication: Low altitude training is similar to sea level training. In contrast to previously published work, moderate altitude training is associated with reduced tissue buffering capacity, no improvement in enzyme activities or capillary density, and may impair sea level performance.